2012
DOI: 10.1111/j.1365-2826.2012.02291.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Cocaine Exposure During Pregnancy Increases Postpartum Neuroendocrine Stress Responses

Abstract: The cycle of chronic cocaine (CC) use and withdrawal results in increased anxiety, depression and disrupted stress-responsiveness. Oxytocin and corticosterone (CORT) interact to mediate hormonal stress responses and can be altered by cocaine use. These neuroendocrine signals play important regulatory roles in a variety of social behaviours, specifically during the postpartum period, and are sensitive to disruption by CC exposure in both clinical settings and preclinical models. To determine whether CC exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 70 publications
2
13
1
Order By: Relevance
“…Plasma oxytocin levels have previously been examined after acute MDMA or chronic MDMA, METH and cocaine exposure . The present study demonstrated that, compared to controls, IVSA METH significantly increased plasma oxytocin levels, which remained elevated after 15 days of extinction.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Plasma oxytocin levels have previously been examined after acute MDMA or chronic MDMA, METH and cocaine exposure . The present study demonstrated that, compared to controls, IVSA METH significantly increased plasma oxytocin levels, which remained elevated after 15 days of extinction.…”
Section: Discussionsupporting
confidence: 56%
“…No changes in CRF-IR fibre staining or plasma CORT concentration were identified when comparing the rats that self-administered METH and the yoked saline rats. Plasma oxytocin levels have previously been examined after acute MDMA or chronic MDMA, METH and cocaine exposure (12,20,35,36). The present study demonstrated that, compared to controls, IVSA METH significantly increased plasma oxytocin levels, which remained elevated after 15 days of extinction.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…On PPD 5, following a pup retrieval task, CC-exposed mothers had reduced plasma Oxt compared to controls, with no differences in brain Oxt in the MPOA, VTA, HIPP or nucleus accumbens (Williams et al, 2011a). However, CC-exposed mothers have higher baseline plasma levels of Oxt, and enhanced plasma Oxt response to stress (the forced swim test), but no altered HIPP or AMY responses (Williams et al, 2012). This suggests that CC-induced changes in Oxt are sensitive to behavioral context.…”
Section: Cocaine’s Effects On Adult Oxytocin Signaling In Rodentsmentioning
confidence: 99%
“…Furthermore, addiction-related increases in anxiety and depression are thought to be partially mediated by overactive stress systems in the brain (Rotzinger et al, 2010; Logrip et al, 2011). The changes in brain and plasma Oxt following cocaine exposure suggest that other social behaviors, stress reactivity or responsiveness to drugs may be altered in chronically drug exposed females which may help explain relapse into addiction or increased postpartum mood disorders observed in these clinical populations (Williams et al, 2012; Rutherford et al, 2011). …”
Section: Cocaine’s Effects On Adult Oxytocin Signaling In Rodentsmentioning
confidence: 99%